The Analysis of Application of Technical Management on Various Small Holder Dairy Farm Scale in Garut Regency West Java - Sopiyana, S (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2006)
The research has been carried out to study and evaluate application of technical management (reproduction, feeding, and daily management) on various small holders dairy Farm scales in Garut regency, West Java. This research used the survey method, and the number of respondent was 82 small holder dairy farms which were divided into 37 respondents on the first dairy cattle farm scales with the ownership of 1-3 cows, 33 respondents on second dairy cattle farm scales with the ownership of 4-6 cows, and 12 respondents on the third dairy cattle farm scales with the ownership of >7 cows. Simple random sampling was used for taking the respondents of smallholder dairy farm. Data were statistically analyzed using the Duncan method of one way ANOVA. The results of this research showed that: (1) Milk yields average on the third dairy cattle farm scale were same as the second and the third dairy cattle farm scales (13.98 vs. 13.91 vs. 13.32 kg) respectively, (2) Farm management level was highest on the third dairy cattle farm scale than both the second and the first dairy cattle farm scales. (Animal Production 8(3): 216-225 (2006)Â Key Words : Technical management, dairy farm, milk yield.